Phase dependent loading of Bloch bands and quantum simulation of relativistic wave equation predictions with ultracold atoms in variably shaped optical lattice potentials. Issue 18 (10th October 2016) - Grossert, Christopher; Leder, Martin; Weitz, Martin
Abstract : The dispersion relation of ultracold atoms in variably shaped optical lattices can be tuned to resemble that of a relativistic particle, i.e. be linear instead of the usual nonrelativistic quadratic dispersion relation of a free atom. Cold atoms in such a lattice can be used to carry out quantum simulations of relativistic wave equation predictions. We begin this article by describing a Raman technique that allows to selectively load atoms into a desired Bloch band of the lattice near a band crossing. Subsequently, we review two recent experiments with quasirelativistic rubidium atoms in a bichromatic lattice, demonstrating the analogues of Klein tunnelling and Veselago lensing with ultracold atoms, respectively.